Survey of IT Governance Influence on Digital Transformation and Bank Organization Performance - Nurul Afifah; Rahmat Mulyana; Lukman Abdurrahman (Sistemasi: Jurnal Sistem Informasi, 2022)
The disruption of emerging technologies, startups, changes in stakeholders' behavior, and the COVID-19 pandemic acceleration have forced many companies to perform a digital transformation (DT). However, the facts show many related investment failures because of poor governance practices. Previous research has proven that IT governance (ITG) has a significant role in improving organizational performance. Unfortunately, few studies still show the ITG mechanisms, structures, processes, and relational influence on successful DT. Recent research has found the hybrid ITG influence on DT, but not their relationship to organizational performance. Therefore, we hypothesized the traditional and agile/adaptive ITG mechanisms influence DT and organizational performance. The survey method was used by distributing a questionnaire to the organization's three lines of defense, from the top-level and IT managers (planners, architects, developers, operations, services, security, and quality assurance) to risk managers and internal auditors. The model was analyzed using Structural Equation Modeling assisted by SmartPLS. Bank B was chosen because the banking industry is greatly affected in the digital era along with the rise of fintech. The results showed a significant correlation between agile/adaptive and traditional ITG mechanisms on DT and a positive impact on organizational performance. This manuscript contributes to researchers exploring the ITG mechanism details for successful DT and practitioners to implement them in related industries.